An investigation into the prevalence and growth of phishing attacks against South African financial targets - Lala, Darshan Magan (Rhodes University, Faculty of Science, Department of Computer Science, 2016)
Phishing in the electronic communications medium is the act of sending unsolicited email messages with the intention of masquerading as a reputed business. The objective is to deceive the recipient into divulging personal and sensitive information such as bank account details, credit card numbers and passwords. Attacks against financial services are the most common types of targets for scammers. Phishing attacks in South Africa have cost businesses and consumers substantial amounts of financial loss. This research investigated existing literature to understand the basic concepts of email, phishing, spam and how these fit together. The research also looks into the increasing growth of phishing worldwide and in particular against South African targets. A quantitative study is performed and reported on; this involves the study and analysis of phishing statistics in a data set provided by the South African Anti-Phishing Working Group. The data set contains phishing URL information, country code where the site has been hosted, targeted company name, IP address information and timestamp of the phishing site. The data set contains 161 different phishing targets. The research primarily focuses on the trend in phishing attacks against six South African based financial institutions, but also correlates this with the overall global trend using statistical analysis. The results from the study of the data set are compared to existing statistics and literature regarding the prevalence and growth of phishing in South Africa. The question that this research answers is whether or not the prevalence and growth of phishing in South Africa correlates with the global trend in phishing attacks. The findings indicate that certain correlations exist between some of the South African phishing targets and global phishing trends.
Keywords: Uncatalogued